The Effect Javanese Chili Extract (Piper Retrofractum Vahl) Administration On The Increase Of Albino Male Mice Libido - Erjon Erjon; Yenni Sriwahyuni; Nilda Lely; Ema Ratna Sari (FITOFARMAKA: Jurnal Ilmiah Farmasi, 2020)
Libido is a sexual desire that is an important part of adult human life. The main active compound of Javanese chili is piperine. Javanese chili is reported to cause increased libido. The study aimed to evaluate the effect of administration Javanese chili extract (Piper retrofractum Vahl) to increase libido in albino male mice. The doses of Javanese chili extract used is 50 mg/kgbw; 100 mg/kgbw; and 200 mg/kg bw given as a single dose for 9 days. The parameters observed were kissing, mounting latency, and mounting frequency of albino male mice. The results showed that the administration of Javanese chili extract at doses of 50 mg/kgbw, 100 mg/kgbw, and 200 mg/kgbw showed faster kissing and mounting latency and higher mounting frequency and significantly different (p0,05) compared to the control group. Increasing the dose of Javanese chili fruit extract gave a very strong correlation to the reduction in kissing and mounting latency (r = -0,951 and r = -0,933), and increased mounting frequency (r = 0,892). From the research results, it can be concluded that the administration of Javanese chili fruit extract can increase the libido of albino male mice and the increase in the dose of Javanese chili extract gives a very strong correlation to the increase in the libido of albino male mice.